Comprehensive Account on Prevalence and Characteristics of Hydatid Cysts in Livestock from Pakistan - Mehmood, Naunain; Arshad, Muhammad; Ahmed, Haroon; Simsek, Sami; Muqaddas, Hira (Korean Soc Parasitology, Seoul Natl Univ Coll Medi, 2020)
Pakistan is at intersection of hyperendemic regions for hydatidosis. Current study aimed to determine the prevalence of hydatid cysts and cyst characteristics in different intermediate hosts (sheep, goats, cattle and buffaloes) across the 4 provinces of Pakistan. A total of 991 sheep, 1,478 goats, 1,602 cattle and 1,343 buffaloes were examined for presence of hydatid cysts during 2 years (January 2016-December 2018). Differences in frequency of hydatidosis were observed with highest overall prevalence in buffaloes (11.9%) and sheep (11.5%). Highest prevalence and burden of infection were observed in older age animals (23.8%, 9.78 +/- 0.49) and females (26.5%, 12.53 +/- 0.67). Data for seasonal prevalence alluded to year-round presence of disease with non-significant statistical difference. Organ predilection indicated liver as the most preferred site of cyst localization followed mainly by lungs. An over-dispersion pattern was observed in all infected animals as majority of cysts belonged <10 cysts per infected host category. Highest percentage of fertile cysts was observed in liver of sheep. Interestingly, solitary form of cysts had higher fertility rate than multiple form. Amid lack of data and wide gap of knowledge, this study would try to fill up the lacunae regarding this neglected tropical disease. Extensive rearing of livestock, unregulated official slaughter and home slaughtering have played role in adaptability of E. granulosus in Pakistan.
Keywords: Hydatid cyst; livestock; prevalence; cyst characteristic; Pakistan